Assessing the potential escapee yield and economic losses of enlarging trawl mesh size : a case study in the inner Gulf of Thailand - Weerapol Thitipongtrakul; Bhujel, Ram C.; Datta, Avishek; Ministry of Agriculture and Cooperatives (MOAC), Thailand; Asian Institute of Technology Fellowship (Pathum Thani, Thailand: Asian Institute of Technology, 2019)
The study of potential impacts of the enlarging cod-end mesh size of pair trawl fishery was conducted by simulating the assumed case scenarios through two estimation models. The first model was used to estimate the potential yield of escaped economic juveniles caused by enlarging cod-end mesh size. Five case scenarios with different escape levels of 10%, 15%, 20%, 25% and 30% were simulated. Eleven important economic species were selected as representatives for the escaped juveniles, comprised of four pelagic species, five demersal species and two cephalopod species. The second model was used to estimate the financial impact on pair trawlers if the cod-end mesh sizes were enlarged from current used to 5.0 em and 6.0 ern respectively. The estimation on the second model was based on the escape rate of previous trawl experiment study. The input fishery data were collected from pair trawl vessels operated in the Inner Gulf of Thailand area from January to December 2018. The required biological data of the selected species, market price of fish, and cost and return of pair trawl fishery were used in estimation. The simulation results demonstrated pair trawlers will occasionally lose their income if the cod-end mesh size was enlarged but it would be compensate by the catch of larger sized escaped fish in the near future. The estimated yield and value of escaped juveniles were increased accordingly as increasing of an escape level. The yield was increased differently by species, however, the overall yield of all selected species was increased. There is slightly economic impact on pair trawlers if the cod-end meshes were enlarged to the larger sizes. They would lose about 3.4% of their total income if the cod-end meshes were enlarged to 5.0 ern, and consequentially lose about 8.9% if it was enlarged to 6.0 ern. It is recommended that the government should provide partial support to trawlers, for persuade them and mitigate the occasional loss during changing period. Thus, further practical trawl experiments should be carried out to support the results of the modeling.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Aquaculture and Aquatic Resources Management, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 2019
Keywords: Marine fishes -- Thailand -- Gulf of Thailand; Fishery management -- Thailand -- Gulf of Thailand; Trawlers (Vessels) -- Thailand -- Gulf of Thailand